Observation of Shubnikov–de Haas Oscillations, Planar Hall Effect, and Anisotropic Magnetoresistance at the Conducting Interface of EuO–KTaO3. Issue 1 (14th December 2020) - Kumar, Nand; Wadehra, Neha; Tomar, Ruchi; Shama,; Kumar, Sanjeev; Singh, Yogesh; Dattagupta, Sushanta; Chakraverty, Suvankar
Abstract: The momentum‐dependent splitting of spin‐bands in an electronic system is known as the "Rashba effect." Systems with the Rashba effect possess a Dirac point in momentum space, which may act as a source of Berry's phase for the conduction electrons of such system. Herein, the Shubnikov–de Haas oscillations (SdH) at the conducting interface of EuO–KTaO3 (KTO) are reported. The observed SdH oscillations suggest the presence of two Fermi surfaces. For both Fermi surfaces, the presence of a Berry's phase is seen. Strong spin–orbit coupling is also observed in this system. The existence of two Fermi surfaces with Berry's phase along with the signature of strong spin–orbit coupling suggest the formation of Rashba spin‐split bands. As in topological insulators, two‐fold planar Hall effect and anisotropic magnetoresistance are also observed in EuO–KTO. Analyzing the SdH, Hall, and magnetoresistance data, the authors draw a possible band diagram near the Fermi surface. Abstract : 2D electron gas (2DEG) at oxide interfaces with Rashba spin‐split bands is promising for spin‐electronic devices. Analyzing Shubnikov–de Haas oscillations, the authors report the presence of Rashba spin‐split bands for the 2DEG present at the interface of EuO–KTaO3 . From the transport data, the authors draw a possible band diagram and conclude that the conical point of the energy spectrum is topological.